Psychological characteristics of educational stress of modern students - Dubczak, Halina (Social Welfare: Interdisciplinary Approach, 2019)
The article presents the results of the empirical research of psychological characteristics of stress reactions that occur during educational activities of modern Ukrainian students. The analysis was performed on a group of 600 students (including 316 university students, 284 students of vocational schools; 283 men and 317 women) aged 15-45 years. Common and distinctive characteristics as for importance, levels, forms, dynamics and stress management techniques are determined for students of universities and vocational secondary schools. The conclusions are made about the need of organization of specifically targeted psychological work with students having high manifestations of educational and examination stress.